Receiving of nanosized colloids based on modificated dtpa molecule labeled with technetium-99m; 7th International Symposium on Technetium and Rhenium - Science and Utilization - Nesterov E. A. Evgeny Alexandrovich; Skuridin V. S. Viktor Sergeyevich; Belyanin M. L. Maksim L'vovich; Нестерова Ю. В. Юлия Владимировна; Sadkin V. L. Vladimir Leonidovich; Rogov A. S. Alexander Sergeyevich; Чикова И. В. Ирина Владимировна (2011, 2011)
Заглавие с титульного листа